ECO - FRIENDLY NATURAL COLORS YIELDING FLOWERING PLANTS OF COLLEGE CAMPUS KILA BHAVAN INDORE DISTRICT (M.P.) – A SURVEY REPORT - Mahajan, Saroj; Upadhya, Padma; Johanson, Malini; Malviya, Neelu (International Journal of Research -GRANTHAALAYAH, 2014)
Color is one of the elements of nature that made the human living more aesthetic and fascinating in the world. They are supposed to be associated with emotions, human qualities, seasons, festivals and passion in our life .I n India, there are more than 450 plants that can yield bright colors. Natural dyes are environment friendly such , turmeric, the brightest ofnaturally occurring yellow color is a powerful antiseptic which revitalizes the skin, (R.Siva,2007)PunicagranatumL. (Anar)LawsoniainermisL.(henna), and manyother common natural color yielding plants(Hussein, 1997)The present study mainly focuses on some important plants having color yielding potential. As many as 25species were screened for coloiouring. These species belonging to25genera and 18families are presented in this paper. The botanical names, family,vernacular name and parts from which color is obtained and the colours fixed after treating withrecommended mordents.Natural colorants derived from flora and fauna are believed to be safe because of its nontoxic, non-carcinogenic and biodegradable in nature (Cristea&Vilarem, 2003). Different parts of the plants were used for the extraction of dyes such asbark , leaves, flowers, etc and different types of mordents were used for fixing the dye into the fabric.Study of available literature shows that several studies werecarried out on natural color yielding plants in the recent past. (A. Rashmiel.al., 2004, Debajitand Tiwari 2005, Gour 2008 and Garget al., 2010) color yielding plants are not properly studied with reference to Madhya Pradesh, (Tiwariand Bharat 2008), (Choudhary and Upadhyay 2011) Present work is undertaken to study the color yielding plants of Sehore district.